Simulation of cascaded H-Bridge multilevel inverter for standalone photovoltaic cell application / Arman Shah Abas - Abas, Arman Shah (2014)
The aim of this project is to analyze the multilevel inverter (MLI) topology in renewable energy field. MLI are being preferred over the conventional two-level voltage source inverters in medium-voltage high-power applications. Among different topologies of MLis, Cascaded H-Bridge (CHB) MLis is considered more suitable converters for Photovoltaic (PV) applications since each PV panel can act as a separate DC source for each CHB module. The Sinusoidal Pulse Width Modulation (SPWM) technique was used to synthesis the output waveform. Closed loop system is preferred when there's a need in regulating the output voltage with the input voltage due to changes in load variation by adjusting the duty cycle of the switching pulses. In this project paper, chapter 1 covers the theoretical and brief introduction on power electronic and the multilevel inverter. The objectives and the research methodology are presented in chapter 2. Brief explanations on the theoretical aspect of the MLI regarding the switching methods, low pass filter and the feedback control for closed loop system are presented in chapter 3. Modeling for the proposed MLI is presented in chapter 4. Chapter 5 covered the simulation results on the switching method, low pass filter and the feedback for the closed loop system. Finally, in chapter 6, the conclusions made after the analysis of the result and also the recommended future work.